Improving Health Literacy of Domestic Household Disinfection Use: Readability of Consumer-Facing Information on Domestic Household Disinfectant Products on Sale in the UK—An Infodemiology Study - John E. Moore; Beverley C. Millar (Hygiene, 2023)
Disinfectants purchased from retail outlets form the cornerstone of infection control and prevention within the domestic household. The growing utilisation of the concept of “hospital-at-home” places greater emphasis on domestic disinfection by the householder in helping to prevent the acquisition of infections within the home. No reports or data exist that indicate how readable the information provided on disinfectants is, which would help householders use disinfectants optimally. The aim of this study was therefore to quantitatively examine the readability (Flesch Reading Ease; Flesch–Kinkaid Grade Level; text metrics) of consumer (public)-facing information (n = 108) of domestic household disinfectants sourced from (i) UK high street supermarket chains (n = 4) and (ii) disinfectant manufacturers (n = 6). The readability of all supermarket and manufacturer information (n = 108) gave a mean Flesch Reading Ease score of 51.7 (target ≥ 60) and a Flesch–Kinkaid Grade Level score of 8.1 (target ≤ 8), thereby failing to achieve readability reference target values. Authors preparing information on the domestic use of disinfectants should be aware of the value of quantitative readability metrics and online tools to help support their writing of such information in order to produce materials which are within target readability values, thereby further supporting health literacy in this population and disinfectant efficacy.